2009
DOI: 10.1515/cclm.2009.339
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated developmental changes in the activated partial thromboplastin time (APTT) and causes of prolonged APTT values in healthy Chinese children

Abstract: Background: The concept of developmental hemostasis has been universally accepted. Physiological reference ranges for coagulation tests are available for infants and children of different ages. However, on Oriental children they are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
5
9
0
1
Order By: Relevance
“…The noticeable positive correlation of FVIII plasma levels with the blood donor’s age is consistent with a large number of publications [10, 33, 34, 35], even if the occasional study does not identify an age dependency [15, 36–38]. In line with other studies [10, 14, 15, 35, 39], a significant association with gender cannot be inferred.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The noticeable positive correlation of FVIII plasma levels with the blood donor’s age is consistent with a large number of publications [10, 33, 34, 35], even if the occasional study does not identify an age dependency [15, 36–38]. In line with other studies [10, 14, 15, 35, 39], a significant association with gender cannot be inferred.…”
Section: Discussionsupporting
confidence: 88%
“…This is also corroborated by a comparison between the normal range of these three parameters, derived from the levels of control cohort 3, with the central 95% ranges of study cohorts 1 and 2 which are almost identical. Due to an inclusion of younger populations and an age spectrum of up to 70 years, some studies have reported larger differences in aPTT [36, 37, 40], FVIII [33, 35] and fibrinogen [41, 42] levels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prolongation of APTT in childhood detected by Actin FS most likely displays the reduced levels of related single coagulation factors VIII, IX, XI and XII. Besides reduced levels of intrinsic factors, the values measured by Pathromtin SL may partially be explained by the higher incidence of transient anticoagulants found in pediatric patients [9][10][11]. Klarmann et al [12]used the same method to measure APTT (Pathromtin SL on the BCS); in summary, the results are very comparable, except for the children < 1 year, who presented with longer clotting times in our study.…”
Section: Discussionsupporting
confidence: 60%
“…This could be explained due to pre-analytic factors that were corrected, for example there are difficulties known regarding sample recovery from pediatric patients such as: anatomical conditions, or anxiety of the child, parent or caretaker. Another possibility is the presence of transitory LA, which correlates with the peak in prevalence of LA around 5 years of age reported by Male et al, corresponding with the age group analyzed in the present study [20] and the levels of LA reported as a cause of isolated prolonged aPTT in literature. These reports exceed the levels that we could confirm in our study (up to 53, 1% v/s 10% respectively) [2] [13] [14] [17] [21].…”
Section: Discussionsupporting
confidence: 84%